2011
DOI: 10.1029/2011gl048318
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent scatter radar study of the terdiurnal tide in the E‐ and F‐region heights at Arecibo

Abstract: We report the analysis of the terdiurnal tide in the meridional wind from 90 to 350 km at a low latitude station. Our data is based on nine days of consecutive observation made by the Arecibo incoherent scatter radar during January 14–23, 2010. The terdiurnal tide is observed to be prominent at E‐region heights in the first four days (Jan. 14–18) and at the F‐region heights in the last five days (Jan. 18–23). The terdiurnal tide is among the two strongest tidal components in both regions. The vertical waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 23 publications
1
35
0
Order By: Relevance
“…However, he did not discuss the vertical structure of the F region tidal waves in winter condition. Based on the Arecibo ISR measurements in January 2010, Gong and Zhou (2011) and Gong et al (2013) revealed the vertical structure of DT, SDT, TDT, and QDT in the F region. Our present observations are consistent with previous Arecibo results in that the DT is the dominant tidal component in the F region during winter, and the phases of the DT and SDT in the F region are largely constant.…”
Section: Resultsmentioning
confidence: 99%
“…However, he did not discuss the vertical structure of the F region tidal waves in winter condition. Based on the Arecibo ISR measurements in January 2010, Gong and Zhou (2011) and Gong et al (2013) revealed the vertical structure of DT, SDT, TDT, and QDT in the F region. Our present observations are consistent with previous Arecibo results in that the DT is the dominant tidal component in the F region during winter, and the phases of the DT and SDT in the F region are largely constant.…”
Section: Resultsmentioning
confidence: 99%
“…With the electric field relatively weak during the second interval, we see that the variation of HmF 2 correlates with the tidal wind very well during night. A detailed study on the terdiurnal tide for the Jan. 14–23 period can be found in Gong and Zhou [2011].…”
Section: Discussionmentioning
confidence: 99%
“…We adopted a linear regularization method used by Sulzer et al [2005] to convert LOS ion velocities to vector ion velocities. The meridional wind (positive southward) in the geomagnetic coordinate is derived using the same approach as that used in Gong and Zhou [2011]. The meridional wind is related to the drift and ambipolar diffusion along the field line via, us=(vitalicapvd)secI, where v ap is the anti‐parallel ion drift, I denotes the dip angle, and v d is the diffusion velocity (positive upward).…”
Section: Data Processing and Presentationmentioning
confidence: 99%
“…Our previous study [Chen et al, 2013] shows that a varying ω decreasing from 0.9 to 0.4 combined with c 1 = c 2 = 2 is better than a constant setting of ω = 0.729 and c 1 = c 2 = 1.49445 for ISS fitting.…”
Section: Particle Swarm Optimizermentioning
confidence: 99%